Sistematización de saberes sobre las formas de crianza de los achuar para complementar y enriquecer los contenidos del área de Ciencias Sociales - Piruch Tiwi, Wampiu Edwin (2018)
An investigation is presented on the SYSTEMATIZATION OF KNOWLEDGE ON THE FORMS OF AGING OF THE ACHUAR TO COMPLEMENT AND ENRICH THE CONTENTS OF THE AREA OF SOCIAL SCIENCES, and for that I have been able to investigate first what is the word upbringing, development of culture, knowledge and social sciences. I have compared between Western life and the life of the Achuar indigenous. This work was carried out in the Achuar community Patukmai with the mothers of the same community and who were interviewed through the interview, these questions do to understand the reality of raising the Achuar: 1 What activities are done so that the child grows healthy ?, 2 Until what months do you start moving the hands ?, 3 How do you move ?, 4 What do you sing to the baby ?, 5 How do you talk ?, 6 How old do you begin to eat? 7 What can not be done with the baby? ¿and why?, 8 What can not be eaten?, 9 What foods can you feed the child to grow strong?, 10 What foods helps brain development?, 11 How do you take care of the children?, 12 How does it feel to have children? And finally I have observed the newborn children and I have seen that some of the babies have been infected by diseases of their own mother's carelessness.